The Role of Lecturers in Strengthening Integrity Character as a Bullying Effort at UIN Sunan Kalijaga Yogyakarta - Eri Setiawan; Abdul Munip; Ika Kartika; Wulandari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The problem of bullying that occurs in the world of education requires a solution to overcome this bullying problem. This research aims to analyze the role of lecturers in strengthening the character of integrity as a bullying effort at UIN SUKA Yogyakarta, so that bullying problems that occur among students do not occur again. This research uses a qualitative method with a case study approach, data collection is by direct observation, interviews and documentation. Data analysis was carried out by researchers by reducing data, displaying data and drawing conclusions. The research results show that the role of lecturers at UIN Sunan Kalijaga Yogyakarta has its own strategy in strengthening the character of integrity so that it has an impact on commendable morals and ethics. The lecturers' strategies in efforts to create anti-bullying include character education and ethical learning, fostering inclusive communities, empowering students to become positive leaders and using case studies and ethical discussions. This strategy was felt by the students to be quite effective, so that students responded well, because students understood and understood the impact on bullying behavior.